Composition of coral species and benthic organism at Tiaka Oilfield, Tolo Bay, Central Sulawesi - Kasim Mansyur; Achmad Rizal; Musayyadah Tis'in; Muh Saleh Nurdin; Nuke Susanti (Tomini Journal of Aquatic Science, 2020)
This research aims to find out the composition of the coral and benthic organisms at Tiaka Oilfield. This study was conducted in July 2015. Monitoring of coral and benthic organisms used line intercept transect and visual census method. The research results indicated that 16 coral species were consisting of 6 genera. Coral species dominated by the genus Acropora. Benthic organisms that live in symbiosis with coral reef ecosystems in the Tiaka Oil Field were found 11 benthic species consisting of 54 species